Puccini's Il trittico - Fisher, Burton D.; Adami, Giuseppe, 1878-1946.; Adami, Giuseppe, 1878-1946.; Forzano, Giovacchino; Forzano, Giovacchino; Forzano, Giovacchino; Forzano, Giovacchino; Puccini, Giacomo, 1858-1924. (Miami : Opera Journeys, 2005)
A comprehensive guide to Puccini's IL TRITTICO (Il Tabarro, Suor Angelica, Gianni Schicchi), featuring insightful and in depth Commentary and Analysis of each opera, a complete, newly translated Libretto for each opera with Italian/English side-by side, and over 50 music highlight examples.
Il tabarro -- Suor Angelica -- Gianni Schicchi.
Il Tabarro ("The Cloak"): libretto by Giuseppe Adami.
Suor Angelica ("Sister Angelica"): libretto by Giovacchino Forzano.
Gianni Schicchi: libretto by Giovacchino Forzano.
Text in English; libretto in English and Italian.
Online resource; title from title screen (International Bibliography of Theatre & Dance with Full Text, August 17, 2012).
Includes discography and videography.
Keywords: Puccini, Giacomo, -- 1858-1924.; Trittico (Puccini, Giacomo); Operas -- Librettos; Opéras -- Livrets; MUSIC -- Genres & Styles -- Opera; Operas -- Librettos